BXCOM: A software for computation of radiation sensing - Eyecioğlu, Önder; El-Khayatt, Ahmed Mahmoud; Karabul, Yaşar; Çağlar, Mustafa; Toker, Ozan; İçelli, Orhan (Taylor & Francis Ltd, 2019)
The main objective of this work is to develop user-friendly software, called BXCOM, for computation of the exposure build-up factor (EBF) and the energy absorption build-up factor (EABF), using geometric progression (G-P) fitting method for element, compound or mixture in the energy region 0.015-15 MeV, and for penetration depths up to 40 mean free path (mfp). Furthermore, BXCOM can generate the equivalent atomic number and five fitting parameters used in the G-P method for mixtures and compounds over an interval of photon energies extended from 0.015 to 15 MeV. In addition, the program is designed to calculate the effective atomic number and effective electron number via the direct method. BXCOM program has been verified by comparing its results with approved data by American National Standards Institute. BXCOM runs under MS Windows (R) operating system. It has an improved user interface that provides examination of material's radiation interaction parameters. Finally, BXCOM allows rapid and reliable calculation of many gamma-ray interaction parameters such as , , , G-P fitting parameters and build-up factors that are essential in a wide range of applications such as radiation shielding, radiotherapy, technology and so on.
WOS: 000469740700001
Keywords: Energy Absorption Build-Up factor; Exposure Build-Up Factor; BXCOM; Software